THE EFFECTIVENESS OF USING MICROSOFT EXCEL IN THE PREPARATION OF CARTOGRAPHIC TASKS IN GEOGRAPHY (Journal of Geography and Environmental Management, 2026)
This article explores the effectiveness of using Microsoft Excel in the preparation of cartographic tasks in geography. Modern technologies of information analysis and visualization of data in the field of cartography provide many opportunities to optimize the process of mapping tasks. This article covered the basic functionality of Microsoft Excel, such as creating tables, formatting data, using formulas and charts to represent geographical data. A survey was conducted in which the participants, consisting of students and teachers of geography, answered questions related to the effectiveness of using Microsoft Excel for mapping tasks. The survey results showed that the use of Microsoft Excel significantly increases the efficiency of the mapping tasks compilation process. The program allows you to simplify and automate many operations, such as calculations, data manipulation and the creation of visual representations. Thanks to the flexibility and convenience of Microsoft Excel, participants could work more efficiently with geographical data and create high-quality cartographic tasks. As shown in the final section, the study confirms that the use of Microsoft Excel is an effective tool for mapping tasks in geography. The results allow us to recommend this software for use in educational institutions and the professional sphere in order to improve the quality of cartographic tasks and optimize the process of their creation.
Keywords: Microsoft Excel program; subject geography; cartographic tasks; preparation of tasks; use of the program